Prediction Method for Anisotropy and Fracture Parameters of Reservoirs with Vertical Fractures Based on Acoustic Logging - MENG Jikun; QI Qiaomu; LI Linxin; LI Xiaobin; ZHENG Qinren (Cejing jishu, 2025)
Fractures have a crucial impact on the storage capacity and permeability of oil and gas reservoirs. Accurate identification and quantitative evaluation of fractures are of vital importance in oil and gas exploration and development. However, due to the limitations of geophysical logging tools, it is difficult to directly obtain the complete elastic stiffness tensor used to describe anisotropic fractured reservoirs. To this end, this paper proposes a method, which can realize the prediction of fracture parameters and quantitative detection of gas-filled fractures in reservoirs with vertical fractures only by using conventional logging data (P-wave velocity, fast/slow S-wave velocity and density). Based on the linear slip theory, this paper deduces the anisotropic parameters (γ, ε, δ) of the fracture medium and the analytical expressions of the fracture parameters. Through the waveform coherence stacking methods and waveform matching inversion method, the multipole acoustic logging waveform data is processed and the relevant parameters are extracted. Through the parameter sensitivity analysis of the system, the differentiated control mechanism of different logging parameters on fracture characteristics is revealed: The S-wave splitting intensity dominate the anisotropic development, while the density selectively regulates the fracture compliance characteristics. Furthermore, the identification of gas-filled fracture can be carried out by the intersection of the fracture normal-tangential compliance ratio and the porosity curve. Practical applications show that this model can rapidly and effectively characterize the parameters of reservoir fractures and their anisotropy, and the results of identifying gas-filled fractures have a high degree of consistency with other logging interpretation results. This method can not only quickly evaluate the fracture properties and anisotropy of the formation, but also effectively identify gas-filled fractures. It has high practical value for the rapid evaluation and quantitative characterization of fractured oil and gas reservoirs.